Accelerated reproduction of the parental lines of white cabbage using rosette plants (steckling) and artificial climate chambers - L. L. Bondareva; A. I. Mineykina (Овощи России)
Relevance. The technology of producing cabbage seeds with the traditional method takes almost 2 years. Its high labor intensity caused the need to search for cheaper methods of selection and seed production. One of the ways to speed up the stages of the selection process is the use of artificial climate chambers. The aim of research is to obtain seeds of promising inbred lines of late maturing white cabbage and hybrid combinations with their participation using rosette plants (steckling) in artificial climate chambers. Materials and Methods. The material was inbred pure lines of 5-6 generations of inbreeding, obtained from promising hybrid combinations of domestic and foreign breeding. The research was conducted in 2023-2024. Sowing in Plantek 64 cassettes was carried out on July 10, then the seedlings were transplanted into vegetative vessels with an optimal volume of 5-6 liters and installed in the open ground for the growth of a leaf outlet. In the phase 10-13 of real leaves, the plugs were placed in an artificial climate chamber. During the growth and development period, biometric and phenological observations were carried out, and an analysis of seed setting was carried out during the hybridization of inbred lines.Results. As a result of research in the study of hybrid seed production under artificial climate chamber conditions, high rates of seed setting in buds under cross-pollination of rosette plants of white cabbage were revealed. Genotypes with high seed set rate under geitenogamous bud pollination were also identified. The weight of 1000 seeds of the studied plants was within the range of 2.5-5.14 g. Genotypes 383-3, 384-2 and 384-7 were selected, which had the highest percentage of seeds in the fractional composition with size more than 2 mm 80.3%, 43.5% and 59.4%, respectively. When genotypes 384-2 and 384-7 were used in hybrid combinations as a maternal component, high quality indicators of the obtained seeds were revealed.Conclusion. For the studied genotypes of white cabbage, when grown in an artificial climate chamber, no significant effect on seed quality was found; the genotype had a greater effect on seed quality indicators.